Faktor Determinan Dalam Perilaku Seksual Pranikah di Usia Remaja: (Literature Review) - Adyani, Kartika; Nasikhah, Dina (Prodi Kebidanan Universitas Islam Negeri Alauddin Makassar, 2025)
Introduction: Premarital sexual behavior among adolescents has become an increasingly concerning issue due to its negative impact on physical, psychological, and social health. Adolescents are in a transitional phase that makes them vulnerable to external influences, such as peer pressure, media exposure, and environmental factors. This study aims to identify various factors influencing premarital sexual behavior in adolescents. Method: The method used is a literature review, based on 10 relevant national and international articles published between 2020 and 2025, obtained through databases such as Google Scholar and PubMed. Result: Statistical findings from the reviewed articles revealed significant correlations (p < 0.05) and high odds ratios (e.g., OR=9.444 for peer influence, OR=47.07 for parental role, and OR=6.718 for religiosity). These findings indicate that adolescents who are exposed to negative peer environments, lack parental guidance, or have limited understanding of sexual health and religion are more likely to engage in risky sexual behavior. Conclusion: Addressing premarital sexual behavior in adolescents requires a comprehensive preventive approach involving families, schools, government institutions, and media regulation to create a healthier developmental environment.